A system for sorting radioactive waste of the Chernobyl exclusion zone - Slabospitzkij, R.P.; Ganenko, V.B.; Bukov, V.T.; Savchuk, O.G.; Selukova, V.V.; Batij, V.G.; Kouzmenko, V.O.; Stoyanov, V.I. (Вопросы атомной науки и техники, 2001)
This work is extending the research started in 1998, which are directed on development of a Chernobyl origin radioactive waste sorting system. In this paper the principal scheme and possible engineering solutions of the system for sorting the waste placed in temporary localization dumps of the Chernobyl Exclusion Zone are described.